Cardiorespiratory, gas-exchange primary kinetics and sensitivity of hypercapnia in endurance athletes: The influence of inspiratory muscle training - Tomiak, T. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Inspiratory muscle training (IMT) may cause changes not only in respiratory muscle power-endurance and lung capacities, but also in cardiorespiratory (CRS) response CO2-sensitivity, perceptual response and lactate kinetics (1,2). Whether or not these benefits and athletes` working capacities can be achieved by only increasing of respiratory muscle possibilities remains open for debate. It was hypothesized that effects of IMT may be linked with increase of CRS response primary kinetics and sensitivity to hypercapnia. The purpose was to determine the effects of IMT to CRS response carbon dioxide sensitivity, fast kinetics and exercise performance. Homogeneous group of male high performance rowers ( Vo2 max = 71,0-73,1 mlkg-1min-1) were randomized into two groups and perform for three weeks (18 session) the same program of preseason training. Ten athletes were assigned to IMT group and twelve athletes were received sham inspiratory training with the same device (control group). IMT group performed ten repetitions (2 min interval) of 30 inhalation-exhalation (Powerlung) two times a day for three weeks with resistance adjusted to allow for 30 breathes to be close about 3 of maximal effort. Before and after IMT athletes tested for VE response sensitivity to CO2 (rebreathing) and primary kinetics (T50) of VO2, VCO2, VE and HR in rowing ergometer exercise at 0,75 VO2 max and performed 2000m all-out rowing simulation. The results showed that IMT produce significant increase in VE response sensitivity (VE/ PACO2): 1,53(0,11) vs. 1,69(0,15) l.min-1 per 1 mm Hg (p<0,05) compared to control: 1,59(0,14) vs. 1,53(0,16) l.min-1 per 1 mm Hg (ns) and in primary kinetics - T50 VE : 39,1(2,7) vs. 31,9 (2,8) s (p<0,05), control - 38,3(2,9) vs. 36,4 (2,7) s (ns); T50VCO2 : 36,9 (2,5) vs. 33,8 (2,9) s (p<0,05), control - 38,0 (2,6) vs. 36,1 (2,8) s (ns) and V50 HR : 21,1 (1,3) vs. 17,6 (1,2) s (p<0,1), control - 20,7 (1,4) vs. 19,1 (1,3) s (ns). There were not significant effects on peak of VO2 in 2000m all-out rowing simulation in both groups. But athletes in IMT group compared with control had significant increase of VE peak, mean power for the first 500m distance. The conclusion was that RMT improved in CRS response primary kinetics. The changes were significantly related to changes of VE sensitivity to carbon dioxide (r=0,67) and VE peak for all-out rowing simulation (r=0,61). In RMT group increase also some measurements of working capacities. It may be related to increase of CRS drive mechanism and to respiratory compensation of metabolic acidosis.